Therapeutic Potential of Antioxidants and Hybrid TEMPOL Derivatives in Ocular Neurodegenerative Diseases: A Glimpse into the Future - Charles E. Amankwa; Bindu Kodati; Nina Donkor; Suchismita Acharya (Biomedicines, 2023)
Reactive oxygen species play a significant role in the pathogenesis of various ocular neurodegenerative diseases especially glaucoma, age-related macular degeneration (AMD), and ocular ischemic stroke. Increased oxidative stress and the accumulation of ROS have been implicated in the progression of these diseases. As a result, there has been growing interest in exploring potential therapeutic and prophylactic strategies involving exogenous antioxidants. In recent years, there have been significant advancements in the development of synthetic therapeutic antioxidants for targeting reactive oxygen species (ROS) in neurodegenerative diseases. One area of focus has been the development of hybrid TEMPOL derivatives. In the context of ocular diseases, the application of next-generation hybrid TEMPOL antioxidants may offer new avenues for neuroprotection. By targeting ROS and reducing oxidative stress in the retina and optic nerve, these compounds have the potential to preserve retinal ganglion cells and trabecular meshwork and protect against optic nerve damage, mitigating irreversible blindness associated with these diseases. This review seeks to highlight the potential impact of hybrid TEMPOL antioxidants and their derivatives on ocular neurodegenerative disorders.